(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To investigate clinical manifestations of congenital aniridia (CA) in Ukrainian children and adolescents. Material and Methods: Twenty four children and adolescents (47 eyes; group 1 of children under 11 years and group 2 of adolescents aged 11 to 18 years) and 5 adult parents (age, 38 to 48 years; group 3) of patients with CA were included in the study. Of these, 72.4% had familial aniridia and 27.6%, sporadic aniridia. The eye examination included gonioscopy, keratometry, ultrasound biometry, ultrasound examination of the anterior and posterior segments, phosphene assessment, and optical computed tomography. Results: Most patients (75.0% in group 1, 86.7% in group 2, and 100% in group 3) had biomicroscopic evidence of complete aniridia. Aniridia-associated keratopathy (AAK) was found in all groups, with differences in clinical manifestations and severity of AAK between groups. Rates of stages A, B, C and D AAK were 0%, 12.5%, 0%, and 0%, respectively, for group 1, 0%, 40%, 20%, and 13.3%, respectively, for group 2, and 0%, 0%, 70%, and 30%, respectively, for group 3. Congenital cataract was found in 81.3% of eyes in group 1, and progressive cataract, in 86.7% of eyes in group 2. The rate of congenital glaucoma with corneal edema and buphthalmos was 12.5% in group 1. The rate of secondary glaucoma in groups 2 and 3 was 60%. Congenital foveal hypoplasia was observed in 93.75% and 93.3% of the eyes in children and adolescents, respectively. In groups 1, 2 and 3, visual acuity was more commonly ≤ 0.1, and 0.1-0.25 in 37.5%, 26.7%, and 20.0% of eyes, respectively. Conclusion: CA is a rare bilateral panocular genetic disorder, which in 93.3-93.8% of our cases was associated with foveal hypoplasia, causing low vision. Clinical manifestations of CA (AAK, glaucoma, cataract, foveal hypoplasia, nystagmus, etc.) were found to increase in severity with age. Parents of aniridic children exhibited the worst state of the eye. Clinical manifestations of CA were more severe, with higher rates of complications, in eyes with familial CA, compared to eyes with sporadic CA.